Convergence of Baum–Katz series for sums whose terms are elements of linear $m$ th order autoregressive sequence - Ilienko, M.; Polishchuk, A. (Ukrains’kyi Matematychnyi Zhurnal, 2023)
UDC 519.21We establish necessary and sufficient conditions for the convergence of the Baum–Katz series for the sums of elements of linear $m$th order autoregressive sequences of random variables.